Comparative Evaluation of the Microleakage of Bulk Fill Composites with Three Different Light Cure Directions (An In Vitro Study) - Zuha Ayad Jaber; Sattar J. Abdul-Zahra Al Hmedat; Zahraa Abdulaali Al-Ibraheemi; Wasna’a M. Abdulridha; Salah M.Ibrahim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Purpose: This study estimated microleakage in vitro in Bulk fill (Class I) composite restorations of premolars under different light directions. Materials and Methods: Freshly extracted 27 healthy premolar permanent teeth were extracted for reasons unrelated to the study, and Filtek P-60TM composite resin was used as the restorative material. Class I restorations were performedand divided into three groups (n = 9): Buccal and lingual light-direction group(BLLD), Tooth Composite bond light-direction group(TCBLD), and occlusal light-direction group(OLD).All groups were subjected to manual thermocycling and were then immersed in 2% methylene blue for 24 h. Subsequently, the samples were washed, dried, sectioned, and observed under a stereoscopic microscope for any cracks. Results: In the BLLD group, no teeth were identified for grades 2 and 3, whereas six teeth (66.7%) did not show filtration (Grade 0), and 3 teeth (33.33%) showed grade 1. For the OLD group, most specimens (55.55%) had (Grade 3) filtration (dye penetration to the pulpal floor), whereas 33.33% of specimens in this group had grade 2. However, only one sample (11.11%) in this group revealed grade 1, and no sample had (Grad 0). Lastly, grade 2 presented the highest prevalence (dye penetration only to the pulpal floor) of the samples in the TCBLD group (44.44%), and 33.3% showed no infiltration, while only 22.22% exhibited grade 1. Conclusions: BLLD did not cause any microleakage, whereas OLD was associated with a higher degree of filtration.